Efficient Irrigation and Water Conservation : Evidence from South India - Fishman, Ram; Gine, Xavier; Jacoby, Hanan G. (World Bank, Washington, DC, 2021)
Widespread adoption of efficient irrigation technologies, including drip irrigation, has been proposed as a means of limiting groundwater overexploitation, especially in the intensively farmed and water-stressed South Asia region. This paper reports on a randomized controlled trial conducted in the Indian state of Andhra Pradesh to evaluate the potential productivity and water-saving benefits of smallholder drip irrigation. A group of well-owners was encouraged to adopt drip irrigation through a subsidy scheme, whereas a control group was left to its own devices. The results indicate that, after three years, the drip group shifted into more remunerative and irrigation reliant crops, enjoyed higher agricultural revenue, and transferred (primarily through cash sales) more of its groundwater to adjacent plots. In terms of groundwater pumping, which has zero marginal price in this setting, there is precisely zero difference between the drip and control groups. The evidence thus suggests that drip adoption in South India, while increasing irrigation efficiency, will not save groundwater.